2014
DOI: 10.1080/07448481.2013.849259
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Investigating the Effect of a Brief Lifestyle Intervention on Freshman-Year Weight Gain

Abstract: Brief intervention to prevent weight gain was not effective in this sample. Future studies should investigate lengthening the intervention to enhance effectiveness and increasing recruitment to improve statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(61 citation statements)
references
References 30 publications
0
61
0
Order By: Relevance
“…As three studies did not report the mean change in body weight and two were not lifestyle programme based , they were excluded from the review. This left 30 studies, from 33 papers , included in the review. The PRISMA flow diagram for the review process of study selection is shown in Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As three studies did not report the mean change in body weight and two were not lifestyle programme based , they were excluded from the review. This left 30 studies, from 33 papers , included in the review. The PRISMA flow diagram for the review process of study selection is shown in Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Of the twenty‐four studies that reported ethnicity or race, nineteen studies recruited a relatively higher proportion of Caucasian, and no studies targeted a specific ethnic group. Five studies had a greater proportion of participants from ethnic backgrounds than Caucasian. One study had almost equal proportions of participants of Caucasian and ethnically diverse backgrounds .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, evidence-based interventions for this group are lacking (Dennis, Potter, Estabrooks, & Davy, 2012;Middleton & Perri, 2014). There is a need for intervention in the first semester and efforts should be tailored for gender.…”
Section: Resultsmentioning
confidence: 99%
“…Undergraduate students typically lead highly stressful lives, facing myriad challenges and demands, including meeting financial responsibilities; balancing school, work, and leisure time; cultivating relationships; satisfying parents or guardians; and making career decisions (Eagan et al, ). Students also begin to make their own lifestyle decisions without close parental supervision, and their choices will establish subsequent health behaviors for the remainder of their lives (Middleton & Perri, ).…”
mentioning
confidence: 99%